The effect of digital literacy, e-commerce business trend, mobile payment, income expectations on intention in digital-based entrepreneurship - Mohamad Bastomi; Junaidi; Agus Hermawan; Puji Handayati (Trigin Publisher, 2023)
This study aims to analyze the effect of digital literacy, e-commerce business trends, mobile payments, and income expectations on intention in digital-based entrepreneurship. The population used in this study were students of the Faculty of Economics and Business, Islamic University of Malang. There were 190 respondents in this study. Data were collected through an online survey of respondents who have an intention in digital entrepreneurship. Partial Least Square (PLS) analysis method was used to test the relationship between independent variables and dependent variables. The results showed that digital literacy and income expectation have a significant positive influence on intention in digital-based entrepreneurship. In contrast, there is no significant effect of e-commerce business trend and mobile payment on entrepreneurial intention. The findings indicate the need to improve digital literacy and understanding of income expectations as an effort to encourage entrepreneurial intention, while strategies related to e- commerce and mobile payment need to be further evaluated. This research provides important insights for stakeholders in understanding the factors that influence intention in digital-based entrepreneurship. The practical implication of this study is the need to improve digital literacy and provide a better understanding of the income potential in entrepreneurship to encourage the creation of new digital-based entrepreneurs.